APPEARED IN:

 Directories: Tutors Workshops Events Sections: Books Camps & Sports Careers Children’s Corner Collected Features Colleges Cover Stories Distance Learning Editorials Famous Interviews Homeschooling Medical Update Metro Beat Movies & Theater Museums Music, Art & Dance Special Education Spotlight On Schools Teachers of the Month Technology Archives: 2014 2013 2012 2011 2010 2009 2008 2007 2006 2005 2004 2003 2002 2001 1995-2000
 JANUARY/FEBRUARY 2016

THE MATH COLUMN
An Infinite Series Fallacy
By Dr. Alfred Posamentier

This is the time of year when we can provide some challenging entertainment – ones that can lead the motivated reader to do some further investigation.  Here is one that will leave many readers somewhat baffled.  Yet the “answer” is a bit subtle and may be require some more mature thought.

By ignoring the notion of a convergent series* we get the following dilemma:

Let S = 1 – 1 + 1 – 1 + 1 – 1 + 1 – 1 + . . .

= (1 – 1) + (1 – 1) + (1 – 1) + (1 – 1) + . . .

= 0 + 0 + 0 + 0 + . . .

= 0

However, were we to group this differently, we would get:

Let S = 1 – 1 + 1 – 1 + 1 – 1 + 1 – 1 + . . .

= 1 – (1 – 1) – (1 – 1) – (1 – 1) –  . . .

= 1 – 0 – 0 – 0 –  . . .

= 1

Therefore, since in the first case, S = 1, and in the second case, S = 0, we could conclude that 1 = 0.

What’s wrong with this argument?

If this hasn’t upset you enough, consider the following argument:

Let S = 1 + 2 + 4 + 8 + 16 +32 + 64 + . . . .                  (1)

Here S is clearly positive.

Also, S – 1 = 2 + 4 + 8 + 16 +32 + 64 + . . . .     (2)

Now by multiplying both sides of equation (1) by 2, we get:

2S = 2 + 4 + 8 + 16 + 32 + 64 + . . .           (3)

Substituting equations (2) into (3) gives us:

2S = S – 1

From which we can conclude that S = – 1.

This would have us conclude that – 1 is positive, since we established earlier that S was positive.

To clarify the last fallacy, you might want to compare the following correct form of a convergent series:

Let S = 1 + (1/2) + (1/4) + (1/8) + (1/16)

We then have 2S = 2 + 1 + (1/2) + (1/4) + (1/8) + (1/16)

Then 2S = 2 + S, and S = 2, which is true.  The difference lies in the notion of a convergent series as is this last one, while the earlier ones were not convergent, and therefore, do not allow for the assumptions we made. #

---------------------

* In simple terms, a series converges if it appears to be approaching a specific finite sum.  For example, the series 1 + (1/2) + (1/4) + (1/8) + (1/16) + (1/32) + L converges to 2, while the series 1 + (1/2) + (1/3) + (1/4) + (1/5) + (1/6 + L does not converge to any finite sum but continues to grow indefinitely.